Gelling behavior of MgAl2O4 slurries with a common dispersant. Issue 7 (29th March 2022) - Liu, Mengwei; Zhao, Jin; Shimai, Shunzo; Han, Dan; Zhang, Jian; Wang, Shiwei
Abstract: MgAl2 O4 transparent ceramics were shaped by a commonly used polyacrylic acid (PAA), which acted as both dispersant and gelling agent. The spinel slurries were prepared by ball‐milling MgAl2 O4 powder, PAA, and water in an attrition mill. The gelling of slurries happened at room temperature in air atmosphere without any other organic additive. The gelling mechanism was the formation of chelates between Mg 2+ and carboxyl groups (‐COO − ) of PAA. The frequency‐based testing method was applied to investigate the gelling process of the as‐prepared slurry. In addition, a novel in situ characterization method based on a modified indentation testing was invented to better understand the strengthening of the wet green body with time and to guide when demolding could be carried out. After sintering, transparent MgAl2 O4 ceramics with high in‐line transmittance were resulted.